ANTIFUNGAL AND SYNERGISTIC EFFECTS OF ZNO NANOPARTICLES AGAINST T.VERRUCOSUM CAUSED RINGWORM IN COWS - H. Y. Khalaf (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
The current study was aimed to determined the main causes of ringworm in cows and antifungal and synergistic effects of ZnO nanoparticles. For this purpose 50  skin scrapes were collected from cows infected with ringworm, culture media, staining and genetic methods used for diagnosis. MIC and MFC for antifungal and ZnO were determined. The result showed that Trichophyton spp was isolated in rate of 76%. The isolation rate of T.verrucosum, T. mentagrophytes  and T. rubrum were 68.4%, 21.0% and 10.5% respectively. MIC of Nystatin, fluocytosin, ZnO, Nystatin+ ZnO  and Fluocytosin + ZnO were 200,150,200,150 and 100 μg/ml  respectively. in conclusion, that  T.verrucosum is main caused of Ringworm and ZnO has antifungal and synergistic effects.